Mainstream partial nitritation and anammox: long-term process stability and effluent quality at low temperatures. (15th September 2016) - Laureni, Michele; Falås, Per; Robin, Orlane; Wick, Arne; Weissbrodt, David G.; Nielsen, Jeppe Lund; Ternes, Thomas A.; Morgenroth, Eberhard; Joss, Adriano
Abstract: The implementation of autotrophic anaerobic ammonium oxidation processes for the removal of nitrogen from municipal wastewater (known as "mainstream anammox") bears the potential to bring wastewater treatment plants close to energy autarky. The aim of the present work was to assess the long-term stability of partial nitritation/anammox (PN/A) processes operating at low temperatures and their reliability in meeting nitrogen concentrations in the range of typical discharge limits below 2  mg NH 4 - N · L − 1 and 10 mgNtot ·L −1 . Two main 12-L sequencing batch reactors were operated in parallel for PN/A on aerobically pre-treated municipal wastewater (21 ± 5 mg NH 4 - N · L − 1 and residual 69 ± 19 mgCODtot ·L −1 ) for more than one year, including over 5 months at 15 °C. The two systems consisted of a moving bed biofilm reactor (MBBR) and a hybrid MBBR (H-MBBR) with flocculent biomass. Operation at limiting oxygen concentrations (0.15–0.18 mg O 2 · L − 1 ) allowed stable suppression of the activity of nitrite-oxidizing bacteria at 15 °C with a production of nitrate over ammonium consumed as low as 16% in the MBBR. Promising nitrogen removal rates of 20–40 mgN ·L −1 ·d −1 were maintained at hydraulic retention times of 14 h. Stable ammonium and total nitrogen removal efficiencies over 90% and 70% respectively were achieved. Both reactors reached average concentrations of total nitrogen below 10 mgN ·L −1 in their effluents, even down to 6 mgN ·L −1 for the MBBR, with an ammonium concentration of 2 mgN ·L −1 (set as operational threshold to stop aeration). Furthermore, the two PN/A systems performed almost identically with respect to the biological removal of organic micropollutants and, importantly, to a similar extent as conventional treatments. A sudden temperature drop to 11 °C resulted in significant suppression of anammox activity, although this was rapidly recovered after the temperature was increased back to 15 °C. Analyses of 16S rRNA gene-targeted amplicon sequencing revealed that the anammox guild of the bacterial communities of the two systems was composed of the genus " Candidatus Brocadia". The potential of PN/A systems to compete with conventional treatments for biological nutrients removal both in terms of removal rates and overall effluent quality was proven. Graphical abstract: Highlights: Stable partial nitritation/anammox of aerobically pre-treated municipal wastewater at 15 °C. Effluent ammonia and total nitrogen concentrations meet current discharge limits. Successful NOB activity suppression at low dissolved oxygen concentrations (0.15–0.18 mgO2 /L). Micropollutants removal comparable to conventional biological treatments. Reversible but dramatic anammox activity suppression during prolonged operation at 11 °C.